Transport and optical effects in self-assembled quantum dot devices - Brown, Adam L. (2009)
This thesis describes a theoretical and numerical study of quantum transport and optical effects through an array of self-assembled InAs quantum dots grown in the intrinsic region of a GaAs p-i-n junction. We present a numerical simulation of this system and compare the generated transport and elecroluminescence results to recent experimental data. The simulation first calculates the quantum tunnelling, excitonic recombination, and relaxation rates within the dots, and then uses a stochastic model to simulate carriers entering and leaving the array. We highlight a number of features within the simulation, which shed light on similar features seen in experimental data. In particular, we demonstrate the importance of including the effects of the Coulomb interactions between the carriers, as this is shown be necessary for the simulated and experimental results to match closely. We also investigate a model of Auger processes which is shown to produce up-conversion luminescence, and study the effect of varying the location of the array within the intrinsic region. Additionally we present a master equation approach, which we use to describe a correlated tunnelling regime, in which the Coulomb interaction between an electron and a hole forces them to tunnel alternately onto a single dot before recombination. We produce current and photon noise predictions for both tunnelling and recombination limited regimes. We also investigate this phenomena for a pair of interacting dots, and find a number of two dot configurations which are able to produce current and electroluminescence. We present current and photo-current rate predictions for each case, and associated current and photon noise results.